Let
![\displaystyle y(x) = \sum_{n=0}^\infty a_nx^n = a_0 + a_1x + a_2x^2 + \cdots](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%28x%29%20%3D%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20a_nx%5En%20%3D%20a_0%20%2B%20a_1x%20%2B%20a_2x%5E2%20%2B%20%5Ccdots)
Differentiating twice gives
![\displaystyle y'(x) = \sum_{n=1}^\infty na_nx^{n-1} = \sum_{n=0}^\infty (n+1) a_{n+1} x^n = a_1 + 2a_2x + 3a_3x^2 + \cdots](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%27%28x%29%20%3D%20%5Csum_%7Bn%3D1%7D%5E%5Cinfty%20na_nx%5E%7Bn-1%7D%20%3D%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20%28n%2B1%29%20a_%7Bn%2B1%7D%20x%5En%20%3D%20a_1%20%2B%202a_2x%20%2B%203a_3x%5E2%20%2B%20%5Ccdots)
![\displaystyle y''(x) = \sum_{n=2}^\infty n (n-1) a_nx^{n-2} = \sum_{n=0}^\infty (n+2) (n+1) a_{n+2} x^n](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%27%27%28x%29%20%3D%20%5Csum_%7Bn%3D2%7D%5E%5Cinfty%20n%20%28n-1%29%20a_nx%5E%7Bn-2%7D%20%3D%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20%28n%2B2%29%20%28n%2B1%29%20a_%7Bn%2B2%7D%20x%5En)
When x = 0, we observe that y(0) = a₀ and y'(0) = a₁ can act as initial conditions.
Substitute these into the given differential equation:
![\displaystyle \sum_{n=0}^\infty (n+2)(n+1) a_{n+2} x^n - \sum_{n=0}^\infty a_nx^n = 0](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20%28n%2B2%29%28n%2B1%29%20a_%7Bn%2B2%7D%20x%5En%20-%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20a_nx%5En%20%3D%200)
![\displaystyle \sum_{n=0}^\infty \bigg((n+2)(n+1) a_{n+2} - a_n\bigg) x^n = 0](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20%5Cbigg%28%28n%2B2%29%28n%2B1%29%20a_%7Bn%2B2%7D%20-%20a_n%5Cbigg%29%20x%5En%20%3D%200)
Then the coefficients in the power series solution are governed by the recurrence relation,
![\begin{cases}a_0 = y(0) \\ a_1 = y'(0) \\\\ a_{n+2} = \dfrac{a_n}{(n+2)(n+1)} & \text{for }n\ge0\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Da_0%20%3D%20y%280%29%20%5C%5C%20a_1%20%3D%20y%27%280%29%20%5C%5C%5C%5C%20a_%7Bn%2B2%7D%20%3D%20%5Cdfrac%7Ba_n%7D%7B%28n%2B2%29%28n%2B1%29%7D%20%26%20%5Ctext%7Bfor%20%7Dn%5Cge0%5Cend%7Bcases%7D)
Since the n-th coefficient depends on the (n - 2)-th coefficient, we split n into two cases.
• If n is even, then n = 2k for some integer k ≥ 0. Then
![k=0 \implies n=0 \implies a_0 = a_0](https://tex.z-dn.net/?f=k%3D0%20%5Cimplies%20n%3D0%20%5Cimplies%20a_0%20%3D%20a_0)
![k=1 \implies n=2 \implies a_2 = \dfrac{a_0}{2\cdot1}](https://tex.z-dn.net/?f=k%3D1%20%5Cimplies%20n%3D2%20%5Cimplies%20a_2%20%3D%20%5Cdfrac%7Ba_0%7D%7B2%5Ccdot1%7D)
![k=2 \implies n=4 \implies a_4 = \dfrac{a_2}{4\cdot3} = \dfrac{a_0}{4\cdot3\cdot2\cdot1}](https://tex.z-dn.net/?f=k%3D2%20%5Cimplies%20n%3D4%20%5Cimplies%20a_4%20%3D%20%5Cdfrac%7Ba_2%7D%7B4%5Ccdot3%7D%20%3D%20%5Cdfrac%7Ba_0%7D%7B4%5Ccdot3%5Ccdot2%5Ccdot1%7D)
![k=3 \implies n=6 \implies a_6 = \dfrac{a_4}{6\cdot5} = \dfrac{a_0}{6\cdot5\cdot4\cdot3\cdot2\cdot1}](https://tex.z-dn.net/?f=k%3D3%20%5Cimplies%20n%3D6%20%5Cimplies%20a_6%20%3D%20%5Cdfrac%7Ba_4%7D%7B6%5Ccdot5%7D%20%3D%20%5Cdfrac%7Ba_0%7D%7B6%5Ccdot5%5Ccdot4%5Ccdot3%5Ccdot2%5Ccdot1%7D)
It should be easy enough to see that
![a_{n=2k} = \dfrac{a_0}{(2k)!}](https://tex.z-dn.net/?f=a_%7Bn%3D2k%7D%20%3D%20%5Cdfrac%7Ba_0%7D%7B%282k%29%21%7D)
• If n is odd, then n = 2k + 1 for some k ≥ 0. Then
![k = 0 \implies n=1 \implies a_1 = a_1](https://tex.z-dn.net/?f=k%20%3D%200%20%5Cimplies%20n%3D1%20%5Cimplies%20a_1%20%3D%20a_1)
![k = 1 \implies n=3 \implies a_3 = \dfrac{a_1}{3\cdot2}](https://tex.z-dn.net/?f=k%20%3D%201%20%5Cimplies%20n%3D3%20%5Cimplies%20a_3%20%3D%20%5Cdfrac%7Ba_1%7D%7B3%5Ccdot2%7D)
![k = 2 \implies n=5 \implies a_5 = \dfrac{a_3}{5\cdot4} = \dfrac{a_1}{5\cdot4\cdot3\cdot2}](https://tex.z-dn.net/?f=k%20%3D%202%20%5Cimplies%20n%3D5%20%5Cimplies%20a_5%20%3D%20%5Cdfrac%7Ba_3%7D%7B5%5Ccdot4%7D%20%3D%20%5Cdfrac%7Ba_1%7D%7B5%5Ccdot4%5Ccdot3%5Ccdot2%7D)
![k=3 \implies n=7 \implies a_7=\dfrac{a_5}{7\cdot6} = \dfrac{a_1}{7\cdot6\cdot5\cdot4\cdot3\cdot2}](https://tex.z-dn.net/?f=k%3D3%20%5Cimplies%20n%3D7%20%5Cimplies%20a_7%3D%5Cdfrac%7Ba_5%7D%7B7%5Ccdot6%7D%20%3D%20%5Cdfrac%7Ba_1%7D%7B7%5Ccdot6%5Ccdot5%5Ccdot4%5Ccdot3%5Ccdot2%7D)
so that
![a_{n=2k+1} = \dfrac{a_1}{(2k+1)!}](https://tex.z-dn.net/?f=a_%7Bn%3D2k%2B1%7D%20%3D%20%5Cdfrac%7Ba_1%7D%7B%282k%2B1%29%21%7D)
So, the overall series solution is
![\displaystyle y(x) = \sum_{n=0}^\infty a_nx^n = \sum_{k=0}^\infty \left(a_{2k}x^{2k} + a_{2k+1}x^{2k+1}\right)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%28x%29%20%3D%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20a_nx%5En%20%3D%20%5Csum_%7Bk%3D0%7D%5E%5Cinfty%20%5Cleft%28a_%7B2k%7Dx%5E%7B2k%7D%20%2B%20a_%7B2k%2B1%7Dx%5E%7B2k%2B1%7D%5Cright%29)
![\boxed{\displaystyle y(x) = a_0 \sum_{k=0}^\infty \frac{x^{2k}}{(2k)!} + a_1 \sum_{k=0}^\infty \frac{x^{2k+1}}{(2k+1)!}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cdisplaystyle%20y%28x%29%20%3D%20a_0%20%5Csum_%7Bk%3D0%7D%5E%5Cinfty%20%5Cfrac%7Bx%5E%7B2k%7D%7D%7B%282k%29%21%7D%20%2B%20a_1%20%5Csum_%7Bk%3D0%7D%5E%5Cinfty%20%5Cfrac%7Bx%5E%7B2k%2B1%7D%7D%7B%282k%2B1%29%21%7D%7D)